Identification of novel dithiocarbamate-copper complexes targeting p97/NPL4 pathway in cancer cells - Loffelmann, Martin; Škrott, Zdeněk; Majera, Dušana; Štarha, Pavel; Kryštof, Vladimír; Mistrík, Martin (European journal of medicinal chemistry, 2023)
Dithiocarbamates (DTCs) are simple organic compounds with many applications in industry and medicine. They are potent metal chelators forming complexes with various metal ions, including copper. Recently, bis(diethyldithiocarbamate)-copper complex (CuET) has been identified as a metabolic product of the anti-alcoholic drug Antabuse (disulfiram, DSF), standing behind DSF's reported anticancer activity. Mechanistically, CuET in cells causes aggregation of NPL4 protein, an essential cofactor of the p97 segregase, an integral part of the ubiquitin-proteasome system. The malfunction of p97/NPL4 caused by CuET leads to proteotoxic stress accompanied by heat shock and unfolded protein responses and cancer cell death. However, it is not known whether the NPL4 inhibition is unique for CuET or whether it is shared with other dithiocarbamate-copper complexes. Thus, we tested 20 DTCs-copper complexes in this work for their ability to target and aggregate NPL4 protein. Surprisingly, we have found that certain potency against NPL4 is relatively common for structurally different DTCs-copper complexes, as thirteen compounds scored in the cellular NPL4 aggregation assay. These compounds also shared typical cellular phenotypes reported previously for CuET, including the NPL4/p97 proteins immobilization, accumulation of polyubiquitinated proteins, the unfolded protein, and the heat shock responses. Moreover, the active complexes were also toxic to cancer cells (the most potent in the nanomolar range), and we have found a strong positive correlation between NPL4 aggregation and cytotoxicity, confirming NPL4 as a relevant target. These results show the widespread potency of DTCs-copper complexes to target NPL4 with subsequent induction of lethal proteotoxic stress in cancer cells with implications for drug development.
Keywords: Ubiquitin; Neoplasms; NPL4 protein; nádory; dithiokarb; Dithiocarbamates; ubikvitin; Cancer; měď; Proteins; Copper; Disulfiram; Proteotoxic stress; proteiny; proteasomový endopeptidasový komplex; Ditiocarb; disulfiram; CuET; Copper complex; Proteasome Endopeptidase Complex